Pyroptosis and respiratory diseases: A review of current knowledge - Sun, Jialiang; Li, Yanan (Frontiers in Immunology, 2022)
Pyroptosis is a relatively newly discovered programmed cell death accompanied by an inflammatory response. In the classical view, pyroptosis is mediated by caspases-1,-4,-5,-11 and executed by GSDMD, however, recently it was demonstrated that caspase-3 and-8 also participate in the process of pyroptosis, by cleaving GSDMD/E and GSDMD respectively. Different from autophagy and apoptosis, many pores are formed on the cell membrane during pyroptosis, which makes the cell membrane lose its integrity, eventually leading to the release of cytokines interleukin(IL)-1β and IL-18. When the body is infected with pathogens or exposed to some stimulations, pyroptosis could play an immune defense role. It is found that pyroptosis exists widely in infectious and inflammatory respiratory diseases such as acute lung injury, bronchial dysplasia, chronic obstructive pulmonary disease, and asthma. Excessive pyroptosis may accompany airway inflammation, tissue injury, and airway damage, and induce an inflammatory reaction, leading to more serious damage and poor prognosis of respiratory diseases. This review summarizes the relationship between pyroptosis and related respiratory diseases.